199 A Novel Selective Inhibitior for Plasma Membrane Calcium Atpase 4 Improves VEGF-Mediated Angiogenesis. (3rd June 2016) - Kurusamy, Sathishkumar; Lopez-Maderuelo, Dolores; Little, Robert; Cadagan, David; Murcott, Clare; Baggott, Rhiannon; Oceandy, Delvac; Rowther, Farjana Begam; Wang, Weiguang; Neyses, Ludwig; Cartwright, Elizabeth; Redondo, Juan Miguel; et al.
Abstract : Cardiovascular diseases such as ischaemic heart disease, peripheral arterial disease and stroke are leading causes of death worldwide. Therapeutic angiogenesis, which can improve the formation of new blood vessels in the ischaemic organ, provides a valuable tool for treating cardiovascular diseases. Angiogenesis, a complex blood vessel formation process, involves the participation of several pro- and anti-angiogenic factors. Among them, pro-angiogenic factor Vascular Endothelial Growth Factor (VEGF) has been identified to play a critical role in pathological angiogenesis. Pre-clinical studies demonstrate that VEGF-based pro-angiogenic therapies result in successful reperfusion of the ischaemic organ in animal models. In our previous study, we reported a novel role for the Plasma Membrane Calcium ATPase 4 (PMCA4) as a negative regulator of angiogenic processes mediated by VEGF. Here, we hypothesised that selective inhibition of PMCA4 with the small molecule aurintricarboxylic acid (ATA) will improve VEGF-driven angiogenesis in vitro and an in vivo model of mouse limb ischaemia. Consistent with this hypothesis, we demonstrate in this work that inhibition of PMCA4 by treatment with ATA significantly increases the activity of calcineurin/NFAT pathway and the subsequent expression of the NFAT-dependent, pro-angiogenic protein RCAN1.4 in VEGF-stimulated endothelial cells. Additionally, ATA treatment reduces the level of membrane-associated calcineurin, suggesting that enhancement of calcineurin signalling is the result of a disruption of the interaction between PMCA and calcineurin. Moreover, ATA treatment strongly enhances endothelial cell motility and capillary-like formation in matrigel assay. Furthermore, ATA significantly enhances MLEC motility in PMCA4 +/+ (wild type), but not in PMCA4 -/- (knock out) cells, conforming that ATA-mediated inhibition of PMCA4 is implicated in the increase of migration exerted by ATA. Importantly, long-term exposure of endothelial cells to ATA has no changes in cell viability, highlighting the potential clinical application of ATA. In this sense, Post-ischaemic reperfusion of ischaemic limbs in animals treated with ATA is significantly higher than in control-treated animals. The data from this study indicated that modulation of the activity of PMCA4 by treatment with ATA might have important clinical applications to promote blood vessel formation in human diseases associated with insufficient angiogenesis.